PENGARUH VAKSINASI INDUK LELE DUMBO (Clarias gariepinus) TERHADAP KELULUSHIDUPAN, PERTUMBUHAN BENIH DAN PRODUKSI IKAN - Triyanto Triyanto; Kamiso H. N.; A. Isnansetyo (Universitas Gadjah Mada, 1996)
In Indonesia, outbreak of MAS on cultured African catfish occurs periodically. The outbreek seems relate closely to quality of fry,. High quality fry and proper handling will ensure the successful of African catfish culture. Vaccination on vrooders is one of methods to produce high quality of African catfish fry. The objectives of this experiment were to know effect of fingerling produced by vaccination brooders on survival., growth rate, and fish production during grow out periode. Female and male brooders were vaccinated by intraperitoneal and intramuscular injection of 0.5 ml vaccine respectively. Unvaccinated brooders were used as control. Those brooders were spawned 2-4 weeks after vaccination. Fry which produced by unvaccinated brooders was reared separately in paddy field pond 15 days for the first nursery rearing. Fingerling produced by the second nursery rearing period was used for grow out for 3 mounths. Results of this experiment indicated that brooders vaccination could increase survival rate and production of African catfish approximately 22.16% and 9.94% from control respectively. However, the length and weight of fingerling produced by vaccinated brooders were lower than fingerling produced by unvaccinated brooders